A Probe on the urban lifestyle centers of Davao City and its users based on the utilitarian and hedonic motivations to rise customer patronage - Evangelista, Stephen Daniele G.; Rosel, Minerva C. (2020)
Among different shopping center typologies, the urban lifestyle center is currently on the rise. A lot of them are being constructed since the 2000?s namely Matina Town Square, Damosa IT Park, Lanang Business, Matina IT Park, The Peak and many more. However, according to the latest statistics from the Business Bureau, commercial complexes are closing down even at aclose parameter with residential zones. In order to prevent the problem, the researcher probed the urban lifestyle centers of Davao City and its users to determine their shopper type and which attractiveness attributes should be prioritized. In order to achieve this, the researcher gathered primary data from the respondents through a survey tool and from the site through an ocular visit. In conclusion, the researcher was able to determine that the atmosphere, orientation and parking attractiveness attributes had the most influence on customers? patronage behavior. Furthermore, the researcher was also able to identify that most of the customers of urban lifestyle centers in Davao City are ?strivers.? The researcher has taken the following details into consideration and used them in creating design guidelines for the proposed project.
Thesis (BS Architecture)--University of the Philippines Mindanao, 2020